First-Principles Investigation of CO Adsorption on h-Fe7C3 Catalyst - Jinzhe Fu; Deshuai Sun; Zhaojun Chen; Jian Zhang; Hui Du (Crystals, 2020)
h-Fe7C3 is considered as the main active phase of medium-temperature Fe-based Fischer–Tropsch catalysts. Basic theoretical guidance for the design and preparation of Fe-based Fischer–Tropsch catalysts can be obtained by studying the adsorption and activation behavior of CO on h-Fe7C3. In this paper, the first-principles method based on density functional theory is used to study the crystal structure properties of h-Fe7C3 and the adsorption and activation CO on its low Miller index surfaces <semantics> ( 1 <mover accent="true"> 1 ¯ </mover> 0 ) , ( 1 <mover accent="true"> 1 ¯ </mover> 1 ) , ( 101 ) , ( 1 <mover accent="true"> 1 ¯ </mover> <mover accent="true"> 1 ¯ </mover> ) </semantics> and <semantics> ( 001 ) </semantics> . It was found that the low Miller index crystal plane of h-Fe7C3 crystal has multiple equivalent crystal planes and that the maximum adsorption energy of CO at the 3F2 point of the <semantics> ( 1 <mover accent="true"> 1 ¯ </mover> 1 ) </semantics> plane is −2.50 eV, indicating that h-Fe7C3 has a better CO adsorption performance. In addition, the defects generated at the truncated position of the h-Fe7C3 crystal plane have a great impact on the adsorption energy of CO on its surface, that is, the adsorption energy of CO on Fe atoms with C vacancies is higher. The activity of CO after adsorption is greatly affected by the adsorption configuration and less affected by the adsorption energy. The higher the coordination number of Fe atoms after adsorption, the higher the CO activity. At the same time, it was found that the bonding of O and Fe atoms is conducive to the activation of CO.